Analytical Psychology : Notes of the Seminar Given in 1925. - McGuire, William (Jung Seminars Ser., 2012)
For C.G. Jung, 1925 was a watershed year. He turned fifty, visited the Pueblo Indians of New Mexico and the tribesmen of East Africa, published his first book on the principles of analytical psychology meant for the lay public, and gave the first of his formal seminars in English. The seminar, conducted in weekly meetings during the spring and summer, began with a notably personal account of the development of his thinking from 1896 up to his break with Freud in 1912. It moved on to discussions of the basic tenets of analytical psychology--the collective unconscious, typology, the archetypes.